Structural stability and thermoelectric performance of high quality synthetic and natural pyrites (FeS2). Issue 28 (27th June 2019) - Zuñiga-Puelles, E.; Cardoso-Gil, R.; Bobnar, M.; Veremchuk, I.; Himcinschi, C.; Hennig, C.; Kortus, J.; Heide, G.; Gumeniuk, R.
Abstract : Single crystalline pyrite of high quality reveals good thermal- and bad electrical conductivities resulting in poor thermoelectric performance. Abstract : Synthetic bulk and natural pyrite from the hydrothermal mine in Schönbrunn (Saxony, Germany) are confirmed to be stoichiometric FeS2 compounds and stable (for thermoelectric applications) up to ∼600 K by combined thermal, chemical, spectroscopic and X-ray diffraction analyses. Natural pyrite with a small amount (<0.6 wt%) of well-defined transition metal carbonates revealed characteristics of a nondegenerate semiconductor and is suitable as a model system for the investigation of thermoelectric performance. In the temperature range 50–600 K both natural and synthetic high quality bulk FeS2 samples show electrical resistivity and Seebeck coefficients varying within 220–5 × 10 −3 Ω m and 4 – (−450) μV K −1, respectively. The large thermal conductivity (∼40 W m −1 K −1 at 300 K) is exclusively due to phononic contribution, showing a well pronounced maximum centered at ∼75 K for natural pyrite (grain size ≤5 mm). It becomes almost completely suppressed in the sintered bulk samples due to the increase of point defect concentration and additional scattering on the grain boundaries (grain size ≤100 μm). The thermoelectric performance of pure pyrite with ZT ∼ 10 −6 at 600 K is indeed by a factor of ∼1000 worse than those reported earlier for some minerals and synthetic samples.